DIGITALISASI MANAJEMEN KEUANGAN MELALUI SISTEM INFORMASI PADA ATRAKSI JOGGING TRACK DI DESA WISATA MENGWI - Putri Agung Pertama Sari; Bagus Putu Wahyu Nirmala (Jurnal Teknologi Informasi dan Komputer, 2024)
Recorded financial management will make it easier for managers to create programs, control, view history and determine future policies. Mengwi Village is one of the tourist villages in Badung Regency, Bali. Its has experienced problems so far because financial recording is still done manually. It is hoped that the digitization of financial management through an information system can help financial management, especially regarding the finances of the jogging track tourist attraction. Digital management of information systems so that they are more accurate and efficient. The Financial Information System in the Mengwi Tourism Village, called SIKU Mengwi, was designed using the waterfall method approach. It is hoped that the SIKU Mengwi will make it easier to record financial transactions, prepare financial reports, increase the accuracy of reports by reducing calculation errors because it has been computed by the system and ultimately help in making policies and program activities for developing the Mengwi Tourism Village.